“Tinea incognita”. A diagnostic challenge. - Montinari, M.; Nemelka, O.; Viglizzo, G.; Bleidl, D.; Occella, C. (European Journal of Pediatric Dermatology, 2009)
"Tinea incognita" is a dermatophyte mycosis, whose aspect is modified by the inappropriate administration of corticosteroids, both topically due to incorrect diagnosis or to the patient's decision, or systemically for other diseases. The incidence of these clinical forms has increased, maybe due to the more frequent "do-it-yourself" use of medications by the general population. Corticosteroids applied locally minimize itching symptoms and modify the inflammatory response, causing dermatosis with often bizarre clinical morphology and difficulty in the diagnosis even by expert dermatologists. This study reports on five recent cases of tinea incognita caused by different etiologic factors.